Presupposition and Entailment Used in Greta Thunberg’s Speech at un Climate Action Summit 2019 - Aini, Nurul; Ariyanti, Lisetyo (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
Climate change is one of the hottest topics lately. Global emissions are reaching record levels and showing no sign of peaking. Antonio Guterres UN Secretary-General invited all leaders to join Climate Action Summit in New York, 23rd September 2019. This summit also featured the participation of business leaders, indigenous people, youth, and many others. The star of the showed Greta Thunberg a Swedish teen activist who sailed to New York for the event from Sweden on a zero-emissions sailboat. This research aimed to reveal how presupposition and entailment were used in the speech and how they were contributing to the context of the speech. The research used a descriptive qualitative method for analyzing her speech which involved document and material analysis to collect the data. The results showed that this research found out that the most commonly used presupposition is existential presupposition. The function is to emphasize, to draw attention and sympathy toward the listeners. While the most used entailment is one-way entailment. This type of entailment is commonly used to deliver the ideas through the utterance by adding some more details of the main idea. Existential presupposition and one-way entailment led to the referential function of language which aimed to send information or the speaker's idea to the audience. It can be concluded that the presuppositions of the speech must be entailed by the global context, which means the global context or common ground knowledge entails that presupposition. In a word, both presupposition and entailment hence become a strategy to make the audience become more focused in the context of the speech. Keywords: Presupposition, Entailment, Speech